Endovascular Treatment of Giant P1/P2 Aneurysm by Direct Puncture of the Vertebral Artery: Case Report - Szajner, M. (Centauro S.r.l., 2003)
Vascular access is usually achieved through a femoral arterial puncture using a modified Seldinger technique. However, selective catheterization of the great cerebral vessels by femoral approach fails completely when the vessel is tortuous or atheromatous. In case of posterior vascular circulation aneurysms, transbrachial approach or direct puncture of the vertebral artery (VA) is an alternative. The aneurysms of the posterior cerebral artery (PCA) are reported to be rare. Due to unfavorable anatomic location, the PCA aneurysms are difficult to reach during surgical procedure. Endovascular embolization is at present considered to be more effective and safer treatment of the PCA aneurysms arising from different segments, offering a viable alternative to the surgical approach. We report the case of the giant left PCA aneurysm, located at the junction of P1/P2 segments, successfully treated by parent artery occlusion achieved after the direct puncture of the right VA which was used because both VAs were tortuous, irregular and their ostia were not accessible by femoral approach. According to different authors, parent artery occlusion appears to be safe in the treatment of P2 segment aneurysms, whatever the location of the occlusion. In our case we decided to perform this kind of treatment believing it was the only possible one.